Simulação de um processo de automação em uma linha de produção de papel higiênico - Basques, Ligiane Alzie (Brasil, 2023)
Automation has great protection in the business sectors of society, such as: health, logistics, residential, internet of things and industry. With all this range of applications, in this TCC an automation project was proposed with the objective of investigating how robotization can be used in the automation of the toilet paper line with the use of industrial robotics. Therefore, the idea was to improve the factory's production process, reduce costs, reduce production time and increase productivity. However, it should be noted how the applicability of these robots may or may not be efficient in the production chain and also in the life of workers in factory environments. From this study, it is concluded that the automation of the production process at the inlet and outlet of the line using robots and an AGV trolley to transport logs requires further studies.